Student’s knowledge on primates: Long-tailed macaque educonservation efforts through primatology course - Budianto, Azzah Kania; Alaydrus, Sayf Muhammad; Miftakhurahma, Rizki; Artaria, Myrtati Dyah (Universitas Negeri Jakarta, 2024)
Within 15 years, the population of Macaca fascicularis has declined rapidly. In early 2022, the IUCN Red List classified them as “Endangered”, though they were considered a species of “Least Concern” in 2008. Land alteration, illegal hunting, and human-macaque conflict often halt long-tailed macaque conservation efforts. Through the Primatology course, anthropology students are taught the importance of macaque conservation and its complications. This preliminary study aims to reveal anthropology students’ knowledge regarding the long-tailed macaque’s status quo and its conservation efforts, pre- and post- their enrolment in the course. Employing a descriptive qualitative approach, this study conducted in-depth interviews with 10 consenting informants—active undergraduate anthropology students. After the transcription process, the data was analyzed by dividing it into multiple subchapters and reviewed with existing literature. More than half of the informants’ knowledge about Macaca fascicularis and primates, in general, is quite satisfactory, though they are still unaware of their current conservation status. According to the informants, cultural and religious factors are closely related to long-tailed macaque conservation, shown in Balinese Hindu temples, Javanese wayang, and topeng monyet. The study concluded that primatology is important because it raises awareness about human’s closest relatives, their ecological significance, and their conservation measures. Adoption or adaptation of the ethnoprimatological framework in biology education as a means of sociocultural exploration and primate conservation is highly recommended. Further research on ethnoprimatology in Indonesia is much needed since Indonesia has many cultural values that might assure the people about contemporary conservation efforts